Toroidal modelling of resonant magnetic perturbations response in ASDEX-Upgrade: coupling between field pitch aligned response and kink amplification. (7th August 2015) - Ryan, D A; Liu, Y Q; Kirk, A; Suttrop, W; Dudson, B; Dunne, M; Fischer, R; Fuchs, J C; Garcia-Munoz, M; Kurzan, B; Piovesan, P; Reinke, M; et al.
Abstract: Using the MARS-F code (Liu et al 2000 Phys. Plasmas 7 3681), the single fluid resistive MHD plasma response to applied n = 2 resonant magnetic perturbations is computed, for a plasma discharge in the ASDEX-Upgrade tokamak. The computation predicts strong kink amplification, as previously predicted in DIII-D (Haskey et al 2014 Plasma Phys. Control. Fusion 56 035005), which is strongly dependent on the toroidal phase shift between the upper and lower coils, . In particular, edge localised low n peeling modes with poloidal mode numbers just above pitch resonance—a subset of the kink response—are amplified. The robustness of the amplified peeling response with respect to truncation of the X point is investigated, by recomputing the plasma response for a range of edge geometries. It is found that the computed peeling response, when plotted against the safety factor, is not sensitive to the numerical truncation near the X point. It is also predicted that near the plasma edge where resistivity is large, the pitch aligned components are finite and also strongly dependent on . A previous proposal that the amplified peeling response may indirectly drive the pitch aligned components by spectral proximity (Lanctot et al 2013 Nucl. Fusion 53 083019), is investigated by numerically applying magnetic perturbations of a single poloidal harmonic, as a boundary condition at the plasma edge. It is found that poloidal harmonic coupling causes harmonics to couple to and drive harmonics directly beneath them spectrally, and also that the pitch aligned components can be driven by this mechanism. This suggests that it is quite possible that the amplified low n peeling response can drive the pitch aligned components when it is strongly amplified, which would alter the coil configuration for optimum plasma stochastization, with implications for ELM control by RMPs.